Transition to sustainability? Feasible scenarios towards a low-carbon economy - Bernardo, Giovanni; D'Alessandro, Simone (Munich, 2014)
"This paper analyses different policies that may promote the transition towards a low-carbon economy. We present a dynamic simulation model where three different strategies are identified: improvements in energy efficiency, the development of the renewable energy sector, and carbon capture and storage. Our aim is to evaluate the dynamics that the implementation of these strategies may produce in the economy, looking at different performance indicators, such as the GDP growth rate, unemployment, labour share, carbon emissions, and renewable energy production. Scenario analysis shows that a number of tradeoffs between social, economic and environmental indicators emerge. Such tradeoffs undermine an `objective' definition of sustainability."